The Behavior of Gangue During the Flotation of a Sulfidic PGM-Bearing Ore in Response to Various Monovalent and Divalent Ions in Process Water - Manono, Malibongwe Shadrach; Corin, Kirsten Claire; Wiese, Jennifer Gael (Frontiers in Chemistry, 2020)
Mineral concentrators are becoming increasingly aware of the importance of the quality of water they feed into their milling and flotation circuits. It is speculated that different inorganic constituents of process water may yield different flotation results owing to electrolyte-reagent-mineral interactions occurring in the pulp phase. These interactions are said to be specific to ion type, reagent type and mineral or ore type. It therefore stands to reason that there is a need to develop an understanding into specific ion effects on both the pulp phase and froth phase phenomena such that the chemistry and quality of process water can be monitored and controlled in a manner that does not negatively affect flotation performance. Previous research has shown that inorganic electrolytes may impact the hydrophobicity and floatability of mineral particles and could in turn affect froth stability, entrainment and thus mineral grades and recoveries. In this study, the floatability of a Cu-Ni-PGM bearing Merensky ore is tested on a bench scale flotation system in various single salt solutions, viz., CaCl2, CaSO4, Ca(NO3)2, MgCl2, Mg(NO3)2, MgSO4, NaCl, NaNO3 and Na2SO4 in order to examine specific ion effects on gangue recovery. Coagulation and zeta potential tests are conducted in order to establish the nature of the impact that specific ions have on the behaviour of gangue in flotation. The findings of this work have shown that single salt solutions containing NO3- ions resulted in a strong depression of gangue compared to those solutions containing Cl- and SO42- ions. It was also shown that the divalent Ca2+ and Mg2+ showed a stronger depression of gangue compared to the monovalent Na+. Ca2+, in comparison to Na+, resulted in an increase in the coagulation of the ore as well as an increase in the zeta potential of talc. Overall, the findings of this paper suggest that the presence of Ca2+ and Mg2+ in process water would most likely create conditions that promotes gangue depression.